Enhancing the Quality of Blended Learning through Six Sigma Methodologies - Rinu Vasanth, C.R.; Vignesh, P.; Kuamri, R. Swapna (International Journal of Social Sciences and Management, 2015)
In the current scenario quality control became mandatory for all the sectors .This study is intended to examine the impact of internet facilities on students’ performance through a Blended Learning as a medium in an academic institution. It was examined, how the Blended Learning encompasses a variety of tools to create flexible, rich learning environments that stimulate learners and maximizes the potential for learning? Another objective is Application of Six Sigma methodology in this study is to improve the medium of learning i.e. internet connectivity through a set of procedures in an effective way. Six Sigma can be again viewed as a discipline or an approach driven by data and methodology for eliminating defects in any process- from manufacturing to transactional and from product to service. Keeping the aforesaid two objectives in mind, data was collected from a sample of 119 students residing in various hostel blocks using stratified random sampling technique. Questionnaire was developed after an extensive literature review to measure the impact of internet connectivity in Blended Learning of the students. The questionnaire to measure was based on the model developed by Shawn M. Glynn (2011).The scale was developed by referring to previous models developed by various authors to measure the impact of internet connectivity in the Blended Learning of the students. The statistical analysis used was reliability statistics, KMO, Bartlett’s test and Factor Analysis. The data was analyzed by SPSS version 20). We observed that application of Six Sigma methodology is useful to improve the medium of learning. DOI: http://dx.doi.org/10.3126/ijssm.v2i1.11520 Int. J. Soc. Sci. Manage. Vol-2, issue-1: 36-39